2001
DOI: 10.1016/s0735-1097(01)01287-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of angiotensin AT1and AT2receptors on the expression, translation and function of the Na+-H+exchanger and Na+-HCO3−symporter in the rat heart after myocardial infarction

Abstract: Angiotensin II via its AT1 and AT2 receptors differentially controls transcriptional and translational regulation as well as the activity of NHE-1 and NBC-1 in the ischemic myocardium and contributes to the control of pH regulation in cardiac tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 49 publications
0
27
0
4
Order By: Relevance
“…Previous studies have also reported increased mRNA expression of NBC associated with cardiac pathology. For example, Sandmann et al (33) reported that mRNA levels of NBC-1 (NBCe) were increased twofold in the rat LV FW after myocardial infarction. In human cardiomyopathic hearts (i.e., ischemic and dilated cardiomyopathy), Khandoudi et al (21) demonstrated that hhNBC (NBCe1) mRNA expression increased, whereas mRNA level of NBCn remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported increased mRNA expression of NBC associated with cardiac pathology. For example, Sandmann et al (33) reported that mRNA levels of NBC-1 (NBCe) were increased twofold in the rat LV FW after myocardial infarction. In human cardiomyopathic hearts (i.e., ischemic and dilated cardiomyopathy), Khandoudi et al (21) demonstrated that hhNBC (NBCe1) mRNA expression increased, whereas mRNA level of NBCn remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…NBCe1 is expressed in the heart, although at a lower abundance than in kidney or pancreas (6,31,140,192,480,684,831). Full-length NBCe1-B has been cloned from human heart cDNA (192), and an antibody directed against the third extracellular loop of NBCe1 immunoreacts with protein in rat and human ventricular myocardial cells (481).…”
Section: V) Circulatory System A) Heart Most Northern Blot Analysesmentioning
confidence: 99%
“…Myocardial ischemia-induced acidification (11,35) and the presence of an endogenous agonist such as ANG II may obviously represent stimulatory events for NBC activity. From our earlier results (19), it was clear that an HCO 3 Ϫ -dependent mechanism contributed to pH i recovery after ischemia in adult rat hearts.…”
Section: Regulation Of Sarcolemmal Nbc Activity By Ang IImentioning
confidence: 99%